New species of Acanthocinini Blanchard, 1845 (Coleoptera, Cerambycidae) from Rondônia state, Brazil and notes on some genera - Nascimento, Francisco E. De L.; Heffern, Daniel (Zootaxa, 2018)
Three new species of Acanthocinini (Coleoptera, Cerambycidae) from Rondônia State, Brazil, are described and illustrated: Leptostylus obrienorum, Nyssodrysina maculosa and Urgleptes curvatum. We also present a brief generic discussion about these genera.